The role of toll like receptor 9 in maintaining gut homeostasis - Matthew G Varga; Henry C Lin (Annals of Systems Biology - Peertechz Publications, 2020)
Toll-Like Receptor 9 (TLR9) is a unique pattern recognition receptor due to its ability to induce either pro- or anti-inflammatory cascades. However, much remains to be elucidated regarding this receptor, such as its localization in different cell and tissue types, the potential epitopes that induce signaling, and how activation of the receptor may result in diverging pathways. Despite these unknowns, the integral role of TLR9 in maintaining gut homeostasis remains clear. In addition to maintaining homeostasis, TLR9 may also have significant potential in treating gut-associated inflammatory diseases such as ulcerative colitis, Crohn's and inflammatory bowel disease via its anti-inflammatory effects. This review will outline some of the key remaining questions regarding the role TLR9 in the gut and highlight its potential utility as a therapeutic target for gastrointestinal disease.